Dual PPARα/γ activation inhibits SIRT1-PGC1α axis and causes cardiac dysfunction - Charikleia Kalliora; Ioannis D. Kyriazis; Shin-ichi Oka; Melissa J. Lieu; Yujia Yue; Estela Area-Gomez; Christine J. Pol; Ying Tian; Wataru Mizushima; Adave Chin; Diego Scerbo; P. Christian Schulze; et al. (JCI Insight, 2019)
Dual PPARα/γ agonists that were developed to target hyperlipidemia and hyperglycemia in patients with type 2 diabetes caused cardiac dysfunction or other adverse effects. We studied the mechanisms that underlie the cardiotoxic effects of a dual PPARα/γ agonist, tesaglitazar, in wild-type and diabetic (leptin receptor–deficient, db/db) mice. Mice treated with tesaglitazar-containing chow or high-fat diet developed cardiac dysfunction despite lower plasma triglycerides and glucose levels. Expression of cardiac PPARγ coactivator 1-α (PGC1α), which promotes mitochondrial biogenesis, had the most profound reduction among various fatty acid metabolism genes. Furthermore, we observed increased acetylation of PGC1α, which suggests PGC1α inhibition and lowered sirtuin 1 (SIRT1) expression. This change was associated with lower mitochondrial abundance. Combined pharmacological activation of PPARα and PPARγ in C57BL/6 mice reproduced the reduction of PGC1α expression and mitochondrial abundance. Resveratrol-mediated SIRT1 activation attenuated tesaglitazar-induced cardiac dysfunction and corrected myocardial mitochondrial respiration in C57BL/6 and diabetic mice but not in cardiomyocyte-specific Sirt1–/– mice. Our data show that drugs that activate both PPARα and PPARγ lead to cardiac dysfunction associated with PGC1α suppression and lower mitochondrial abundance, likely due to competition between these 2 transcription factors.